Motivasi Belajar Siswa dalam Berliterasi di SD Negeri Kebonsari Kulon 6 Kota Probolinggo - Susilowati, Yuni; Prihatini, Arti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Student learning motivation can be associated with information skills in learning Indonesian. The focus of this research is on three things, namely (1) the results of students' motivation in literacy; (2) literacy AKM (Minimum Competency Assessment); (3) the correlation between learning motivation and AKM literacy of students at Kebonsari Kulon 6 Public Elementary School, Probolinggo City. Quantitative research with descriptive statistical analysis was used as a research method for fifth grade students who took the AKM test by the Teaching Campus Program Batch 3. Questionnaires and tests were used for data collection techniques. In analyzing the results, it’s strengthened by the theory of learning motivation by Duncan and Mckeachie which has six aspects in measuring learning motivation including anxiety, self-confidence, belief control, task value, extrinsic orientation goals, and intrinsic orientation goals. The results of this study revealed that students learning motivation and AKM literacy were very high but the correlation value between the two was still very weak. This can be seen from several factors, which include students' understanding of the AKM Literacy question and the preparation of learning strategies that have high quality and are effective.